TRAIL receptor–mediated JNK activation and Bim phosphorylation critically regulate Fas-mediated liver damage and lethality - Nadia Corazza; Sabine Jakob; Corinne Schaer; Steffen Frese; Adrian Keogh; Deborah Stroka; Daniela Kassahn; Ralph Torgler; Christoph Mueller; Pascal Schneider; Thomas Brunner (2006)
TNF-related apoptosis-inducing ligand (TRAIL) is a member of the TNF family with potent apoptosis-inducing properties in tumor cells. In particular, TRAIL strongly synergizes with conventional chemotherapeutic drugs to induce tumor cell death. Thus, TRAIL has been proposed as a promising future cancer therapy. Little, however, is known regarding what the role of TRAIL is in normal untransformed cells and whether therapeutic administration of TRAIL, alone or in combination with other apoptotic triggers, may cause tissue damage. In this study, we investigated the role of TRAIL in Fas-induced (CD95/Apo-1-induced) hepatocyte apoptosis and liver damage. While TRAIL alone failed to induce apoptosis in isolated murine hepatocytes, it strongly amplified Fas-induced cell death. Importantly, endogenous TRAIL was found to critically regulate anti-Fas antibody-induced hepatocyte apoptosis, liver damage, and associated lethality in vivo. TRAIL enhanced anti-Fas-induced hepatocyte apoptosis through the activation of JNK and its downstream substrate, the proapoptotic Bcl-2 homolog Bim. Consistently, TRAIL- and Bim-deficient mice and wild-type mice treated with a JNK inhibitor were protected against anti-Fas-induced liver damage. We conclude that TRAIL and Bim are important response modifiers of hepatocyte apoptosis and identify liver damage and lethality as a possible risk of TRAIL-based tumor therapy.